The Influence of Leadership Style, Work Ethic, and Organizational Culture on Employee Performance at PT. Luar Biasa Technology - Ani, Ayu Asri; Kirana, Kusuma Chandra; Purnamarini, Tri Ratna (Dinasti Publisher, 2024)
The study investigates the influence of leadership style, work ethic, and organizational culture on employee performance at PT. Luar Biasa Technology, Yogyakarta. Employing a quantitative approach, data was collected through questionnaires administered to a sample of 54 employees. The collected data was analyzed using SPSS (Statistical Package for the Social Sciences) software. Various statistical techniques were applied, including validity and reliability tests to ensure data integrity, descriptive statistics to provide an overview of the respondents' characteristics and summarize the investigated variables, and multiple regression analysis to examine the impact of leadership style, work ethic, and organizational culture on employee performance. Hypothesis testing was conducted using t-tests and F-tests, while the coefficient of determination (R-squared) was calculated to measure the explanatory power of the independent variables. The findings reveal that leadership style, work ethic, and organizational culture have a significant positive impact on employee performance, both partially and simultaneously. The results align with previous research, emphasizing the importance of these factors in driving employee productivity and success. Practical implications suggest that companies should focus on enhancing leadership practices, fostering a strong work ethic, and cultivating a supportive organizational culture to optimize employee performance.